2009
DOI: 10.1177/0739986309347447
|View full text |Cite
|
Sign up to set email alerts
|

“The Price of Being Mexican”: Sentencing Disparities Between Noncitizen Mexican and Non-Mexican Latinos in the Federal Courts

Abstract: With the increasing discourse about a crime-immigration nexus and Latinos, it is critical to ascertain how the criminal justice system responds to noncitizen Latino defendants. Using federal sentencing data to investigate the role of national origin and immigration status on noncitizen Latinos’ sentencing outcomes, several findings emerge. First, national origin conditions the sentences received for Mexicans and non-Mexican Latinos. Second, immigration status perpetuates disparities among defendants within eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 20 publications
2
42
0
Order By: Relevance
“…Despite sentencing reforms and laws targeted at producing equitable treatment, scholarly responsiveness to the matter continues to find unwarranted disparities based on a number of extralegal factors. Although much of the attention has focused on disparities predicated on race/ethnicity, results from an increasing number of studies are suggesting an even greater need to investigate the influence of citizenship status (Logue 2009;Demuth 2002;Hartley and Armendariz 2011;Wolfe, Pyrooz and Spohn 2011;Light 2014). In fact, Light (2014) found that not only were noncitizens treated more harshly at sentencing but she also found that disparity between citizens and noncitizens at punishment was larger than the disparity between white and minority offenders.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite sentencing reforms and laws targeted at producing equitable treatment, scholarly responsiveness to the matter continues to find unwarranted disparities based on a number of extralegal factors. Although much of the attention has focused on disparities predicated on race/ethnicity, results from an increasing number of studies are suggesting an even greater need to investigate the influence of citizenship status (Logue 2009;Demuth 2002;Hartley and Armendariz 2011;Wolfe, Pyrooz and Spohn 2011;Light 2014). In fact, Light (2014) found that not only were noncitizens treated more harshly at sentencing but she also found that disparity between citizens and noncitizens at punishment was larger than the disparity between white and minority offenders.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While some studies found no evidence of an influence of citizenship on sentence outcomes (Everett and Wojkiewicz 2002;Feldmeyer et al 2015) the results of others (Wolfe et al 2011;Light 2014;Wu and D'Angelo 2014) detect sentencing variation grounded on the citizenship status of the defendant. A smaller, but growing body of sentencing research (Iles 2009;Logue 2009;Orrick and Piquero 2015) has gone beyond citizenship status to explore the effects of national origins. Iles (2009), for example, disaggregated the legal alien category in her study into four groups (South Americans/Mexican immigrants; Dominican Republic; Caribbean nations; and all other countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…enhancement of law enforcement under the Southwest Border Initiative). Coupled with the war on drugs, these efforts have increased the attention on illegal border traffic and resulted in an explosive number of immigration prosecutions in federal courts (Logue, 2009). …”
Section: Introductionmentioning
confidence: 98%
“…Logue () takes the opposite approach. Her investigation looked at Mexicans compared to non‐Mexican Latinos in federal courts but limited the analysis to only noncitizens, thus precluding an examination of Hispanic ethnicity and citizenship.…”
mentioning
confidence: 99%